Prenatal echocardiography diagnosis of a novel combination of bilateral ductus arteriosus and cardiovascular anomalies: a case report and literature review - Zhang, Simin; Wang, Ning; Qu, Pengfei; Shu, Xiaobin; Mi, Yang; Gao, Xinru (Frontiers in Cardiovascular Medicine, 2024)
Background Bilateral ductus arteriosus (BDA) is a relatively rare vascular malformation. According to the double arch theory, BDA is formed when the distal ends of the sixth pairs of primitive arches on the left and right sides have not regressed. We describe a fetus with prenatal echocardiographic findings of BDA and right aortic arch mirror-image branching (RAA-MIB) combined with congenital heart disease. Furthermore, to gain a deeper understanding of the embryological mechanism of BDA, we review the literature on all combinations of BDA present in 40 fetuses/infants. Case summary A 22-year-old female patient underwent fetal echocardiography at 23 weeks of gestation. Both the two-dimensional (2D) grayscale image and color Doppler flow imaging (CDFI) revealed dextro-transposition of the great arteries combined with a ventricular septal defect and RAA-MIB. The following scan revealed a rare vascular ring, which was identified as BDA extending from the confluent of the left pulmonary artery and right pulmonary artery, completely encircling the trachea to form an “O”-shaped vascular ring before finally converging into the descending aorta. A persistent left superior vena cava was also observed. We subsequently used four-dimensional (4D) color Doppler imaging with the spatiotemporal image correlation (STIC) HD live flow and STIC HD live flow silhouette mode to clearly display ventricular arterial connectivity and the direction of vessel travel. Adjusting the image quality and display angle is very important when applying STIC. The 4D images confirmed our diagnosis. After multidisciplinary counseling and discussion with her family, this female patient decided to terminate the pregnancy. Conclusion Our review of the literature summarized nine combinations classified into three types of BDA and aortic arch pathology. However, our case differs because it is a novel combination of intracardiac structural abnormalities and vascular rings in a fetus. Prenatal ultrasound diagnosis of BDA is important and requires a combination of 2D grayscale, CDFI, and STIC images to assist in scanning.